Hydroxytyrosol modulates the levels of microRNA-9 and its target sirtuin-1 thereby counteracting oxidative stress-induced chondrocyte death. Issue 4 (April 2017) - D'Adamo, S.; Cetrullo, S.; Guidotti, S.; Borzì, R.M.; Flamigni, F.
Summary: Objective: Nutraceutical compounds, such as hydroxytyrosol (HT), have been found to exert protective effects in osteoarthritis (OA) by affecting a variety of key molecular and cellular processes in chondrocytes. However, to our knowledge, no relationship has been reported between nutraceuticals and microRNA (miR) network in OA models. Here, we identified a miR that is implicated in HT-mediated chondroprotection following oxidative stress condition by targeting sirtuin-1 (SIRT-1). Methods: Human primary and C-28/I2 chondrocytes were pre-treated with 100 μM HT 30 min before 100 μM H2 O2 addition. In silico analyses were exploited to select putative candidate miRs able to target SIRT-1 mRNA. Luciferase-based gene reporter assay was employed to demonstrate the direct link between miR-9 and its putative mRNA target. Transient transfection approach was performed to examine the effects of miR-9 levels on caspase activity, cell viability and expression of OA-related genes. Results: MiR-9 was identified and confirmed as a post-transcriptional regulator of SIRT-1. MiR-9 and SIRT-1 levels showed opposite changes in chondrocytes following H2 O2 and HT treatment. Moreover mir-9 silencing inhibited cell death induced by H2 O2 partly through down-regulation of SIRT-1, whereas miR-9 overexpression markedly reduced the protective effect of HT. The manipulation of miR-9 levels also resulted in the modulation of OA-related gene expression, including MMP-13, VEGF and RUNX-2. Conclusions: These results show that miR-9 is a critical mediator of the deleterious and OA-related effects of oxidative stress in chondrocytes and that modulation of miR expression may be a crucial mechanism underlying the protective action of HT.